HOUSEHOLD INSURANCE AWARENESS VS. INSURANCE SALES IN POLAND - Niedziółka, Monika (Management and Administration Journal, 2023)
The insurance market world-wide is developing dynamically. New products are being created, but current offers are also being improved; albeit they come with new areas of responsibility. Changes in the market and insurance products are also visible in Poland. Although they are not so dynamic as in the countries of Western Europe, an increase in sales of mainly non-life insurance has been noted year on year. That said, the dynamics of these changes is much lower than in other European countries; as is the expenditure on insurance. So the question arises, what is the cause of this situation? Could it be due to low insurance awareness? Insurance awareness is not only defined in the work as the state of knowledge of the insurance company’s client, but also as the ability to find and use this knowledge and information, to choose a product consciously, to assess this product properly, and the ability to make independent decisions based on objective information, and not subjective opinions and views. The article attempts to assess insurance awareness and the factors that define and influence the same. The work uses the available bibliography, statistical data from the Central Statistical Office, as well as the data from the Polish Chamber of Insurance and the Polish Financial Supervision Authority. An original survey was also conducted, and its results are presented in the last part of the article. As a result of the study, it turned out that insurance sales in Poland are growing. If only on this basis, insurance awareness is assessed, it can be said that the sales are also growing year on year. The respondents of the conducted survey highly assessed their knowledge of the insurance market and products. Unfortunately, the verification of their actual knowledge did not confirm this self-assessment. The average grade was only “satisfactory”; if we followed school grades. The dominant sources of information on insurance, apart from the knowledge of insurance agents, are, primarily, the Internet, as well as friends and family. These sources cannot be treated as fully objective.